Algunos aspectos del estudio de la mentalidad rusa - Ležneva, T. (Eslavística Complutense, 2003)
The russian is an important point for scientific research. It influences on the all parts of peoples life. Besides many different features and aspects of Russian character, family is very important one. The basic principles of the national mentality are transferred from one generation to another in the family by various forms of Russian folklore. The analysis of Russian fairy-tales and proverbs shows the main specific characteristics of Russian mentality.